Inclusive Business Models for SMEs Growth in Malaysia: Proposed Model - Wan Muhammad Idham Wan MAHDI; Wan Fauziah Wan YUSOFF; Abd. Razak AHMAD (Communications of International Proceedings, 2021)
The contribution of Small-Medium Enterprises (SMEs) has become a veritable instrument for promoting entrepreneurial capitalism in developing countries worldwide. In recent years, many developing countries have started leveraging SMEs' advantage to stimulate economic growth through an inclusive business model (IBM). The term IBM has been used to describe strategic management approach involving large companies and SMEs that target bottom-of-pyramid (BOP) consumer markets with the potential to improve access to essential goods and services for the poor (ADB, 2016; Briones, 2011). In this regard, SMEs play a significant role in contributing to society's well-being by providing job opportunities and better quality of products and services. Although IBM has been successfully implemented in many developing countries (Vietnam, the Philippines, Kenya, Ethiopia, etc.), Malaysia is not yet included into the list. However, the issue has been highlighted in the new National Entrepreneurship Policy 2030. The SME Corp (2019a) reported that the problem was due to the model that not fully understood by large Malaysian companies, SMEs, and policymakers. In fact, to date, no study on IBM was found in Malaysia. Therefore, this study aims to analyze the understanding, acceptance, factors, and challenges of IBM's implementation in Malaysia. This study expected to contribute at least three primary outcomes; (1) theoretical development and framework for IBM in Malaysia; (2) providing feedback to the government to improve SMEs performances and well-being society; and (3) providing some suggestions to policymakers to improve related policies on SMEs development and entrepreneurship.
Keywords: Inclusive Business Models; Well-Being Society; Bottom of the Pyramid (BOP); B40